(untitled) (Journal of Guidance and Counselling Studies, 2021)
The study determined the effects of the self instruction technique on stealing tendency among secondary school students in Anambra State. One research question was answered and one hypothesis were tested at 0.05 level of significance. The population size was 201 students, 100 male JS II and 101 female students purposively drawn from three co-educational secondary schools in Awka Education Zone, in Awka South Local Government Area of Anambra State. The sample size was 73 students, 37 males and 36 females who were selected with the aid of 20 self-constructed but validated instruments, used for data collection as questionnaire on students’ stealing tendency (QSST), which had four columns (1, 2, 3, 4). The instruments were validated by two experts from Guidance and Counselling Department and one expert from the Measurement and Evaluation Department of Nnamdi Azikiwe University, Awka. The reliability coefficient value of 0.72 was obtained using Pearson-product Moment Correlation. Mean scores and analysis of co-variance (ANCOVA), were used in answering the one research question and hypothesis respectively. The findings of this study revealed that self instruction technique, was effective on stealing tendency among secondary school students in Awka Education Zone, Anambra State, who were identified with stealing tendencies. In line with the above findings, it was recommended that guidance counsellors, teachers, and parents must guide, explain and discuss the detrimental consequences of stealing tendencies, role model their children/students behaviours and make sure that stealing tendency is not rewarded. However, if they still commit compulsive stealing tendency, the attention of an expert should be drawn.